Role of neck dissection in metastatic squamous cell carcinoma to the parotid gland. (4th August 2016) - Park, S W; Eade, T; Pang, L; Wignall, A; Veivers, D
Abstract: Objective: To investigate the rate of occult neck disease in patients with metastatic squamous cell carcinoma to the parotid gland following parotidectomy and neck dissection. Methods: A consecutive series of patients treated between 2000 and 2014 for metastatic squamous cell carcinoma to the parotid were analysed. Patients were included if they had no clinical or radiological evidence of neck disease. Pathology of parotidectomy and neck dissection specimens was reviewed. Other variables analysed included patient immune status, surgery type, complications, use of positron emission tomography scanning and treatment with radiotherapy. Results: Sixty-five patients had no clinical or radiological evidence of neck disease initially. Forty-six patients (70.8 per cent) underwent neck dissection. Occult neck disease was only found in 8 of the 46 patients (17.3 per cent). Occult neck disease was found more often in those with immunocompromise (5.7 vs 38.5 per cent, p = 0.003). Patients who were immunocompromised had a significantly worse disease-specific survival rate at five years (0 vs 92 per cent, p = 0.0001). Conclusion: Occult neck disease was seen in 17.3 per cent of patients and immunosuppression was a significant predictor for this.